Qur'anic Wealth Management (At-Tamwil) and Digital Waqf Transformation in Indonesia: A Systematic Literature Review - Widya Khaidir; Nurul Muyasaroh; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (Yayasan Darussalam Bengkulu, 2026)
Background: As Islamic financial technology (fintech) continues to expand rapidly, the digitalization of waqf presents a strategic opportunity that is both timely and urgent. However, much of the existing scholarship has concentrated narrowly on jurisprudential rulings and technical feasibility, leaving the deeper normative foundations of the Qur'an as a source of Islamic wealth stewardship largely unexplored. Method: This study aims to examine the Qur'anic concept of wealth management (at-tamwīl) through thematic exegesis (maudhū'ī tafsir), and to develop a framework that integrates these principles with digital waqf innovation in Indonesia. A qualitative descriptive design was employed, combining thematic Qur'anic interpretation as its primary approach with a Systematic Literature Review (SLR) following the PRISMA protocol. Results: The study identifies five core at-tamwīl principles derived from the Qur'an: istikhlaf (trusteeship and accountability), tanmiyah wa tazkiyah (growth and purification), tawazun wa 'adl (balance and distributive justice), tasylif wa bayyinah (clarity and evidentiary transparency), and maqashidiyyah (public welfare orientation). These principles are integrated into the